Effect of Day 3 and Day 5/6 Embryo Quality on the Reproductive Outcomes in the Single Vitrified Embryo Transfer Cycles - Wang, Ningling; Zhao, Xinxi; Ma, Meng; Zhu, Qianqian; Wang, Yao (Frontiers in Endocrinology, 2021)
Objective: To explore the live birth rate and neonatal outcome after single vitrified blastocyst transfer versus single vitrified cleavage-stage embryo transfer at different grades of embryo quality. Methods: A retrospective cohort study including 6077 single vitrified-thawed embryo transfer cycles was performed in the time-period from January 2013 to December 2018. Results: After controlling for potential confounding variables, there are 161% increased odds of a live birth after transfer of single good quality embryo at day 5, 152% increased odds of a live birth after transfer of single poor quality embryo at day 5, 60% increased odds of a live birth after transfer of single good quality embryo at day 6 compared with transfer of single good quality embryo at day 3. Results from the generalized estimated equation regression showed significant relationship of unadjusted birth weight with development stage of embryo and embryo quality (good quality embryo on day 5 vs. Good quality embryo on day 3:β=108.55, SE=34.89, P=0.002; good quality embryo on day 6 vs. Good quality embryo on day 3:β=68.80, SE=33.75, P=0.041). However, no significant differences were seen in birth weight between transfer single poor quality embryo on day 5, 6 and transfer single good quality embryo on day 3. Conclusion: A significant increase in live birth rate and birth weight after transfer of single good quality embryo on day 5 and day 6 compared with transfer of single good quality embryo on day 3 in the vitrified embryo transfer cycles.